2003
DOI: 10.1002/chem.200204570
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Metathesis Processes, [Tp(PH3)MR(η2‐HCH3)] → [Tp(PH3)M(CH3)(η2‐HR)] (M=Fe, Ru, and Os; R=H and CH3)

Abstract: Theoretical calculations on the metathesis process, [Tp(PH3)MR(eta 2-H[bond]CH3)] --> [Tp(PH3)M(CH3)(eta 2-H[bond]R)] (M=Fe, Ru, and Os; R=H and CH3), have been systematically carried out to study their detailed reaction mechanisms. Other than the one-step mechanism via a four-center transition state and the two-step mechanism through an oxidative addition/reductive elimination pathway, a new one-step mechanism, with a transition state formed under oxidative addition, has been found. Based on the intrinsic rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 67 publications
11
59
0
1
Order By: Relevance
“…In a subsequent paper, Lam et al compare the behavior of Fe, Ru, and Os in the metathesis processes shown in Equation (5) (M = Fe(Tp)(PH 3 ), Ru(Tp)(PH 3 ), Os(Tp)(PH 3 )) via DFT calculations. [88] ½MH þ CH 4 …”
Section: Mh(ch 2 R) Via M(h 2 -H-ch 2 R)mentioning
confidence: 99%
“…In a subsequent paper, Lam et al compare the behavior of Fe, Ru, and Os in the metathesis processes shown in Equation (5) (M = Fe(Tp)(PH 3 ), Ru(Tp)(PH 3 ), Os(Tp)(PH 3 )) via DFT calculations. [88] ½MH þ CH 4 …”
Section: Mh(ch 2 R) Via M(h 2 -H-ch 2 R)mentioning
confidence: 99%
“…2). 16 Even more striking was the changing nature of the C-H activation process. With M = Os 'normal' 3-centred oxidative addition was characterised, but with the Ru and Fe analogues 4-centred transition states were seen.…”
Section: Sbm At L N M-r Bonds (R = Alkyl or Aryl)mentioning
confidence: 99%
“…Intermediate between these extremes is a composite of the two transition states where the end result is a σ-bond metathesis mechanisms, but the metal is highly involved in bonding to the hydrogen in the transition state. This type of composite transition state has several names for nuanced versions, such as oxidatively added transition state (OATS) [50,51], metal-assisted σ-bond metathesis (MAσBM) [52,53], or σ-complex assisted metathesis (σ-CAM) [54]. Hall and Vastine [55] have shown that using atoms-inmolecules analysis provides a framework to understand the entire set of transition states along this mechanistic continuum.…”
Section: Cr King Et Almentioning
confidence: 99%